Pengaruh Konsumsi Kurma (Phoenix Dactylifera) Terhadap Kenaikan Kadar Hemoglobin Pada Ibu Hamil Trimester Ii Di Wilayah Puskesmas Kediri - Eny Sendra; Susanti Pratamaningtyas; Ardi Panggayuh (Akademi Keperawatan Dharma Husada Kediri, 2016)
Anemia in pregnancy is a national problem because it reflects the value of socio-economic welfare of society, and a very large influence on the quality of human resources. Pregnant anemia called